From Subordination to Authority: Women’s Negotiation in Pesantren’s Patriarchal Order - Sinta Bella; Helmi Syaifuddin; Jamilah (Program Studi Pendidikan Agama Islam, Fakultas Tarbiyah, Institut Agama Islam (IAI) Ibrahimy Genteng Banyuwangi, 2026)
This study begins with the reality that pesantren as traditional Islamic educational institutions often maintain patriarchal structures that place women in subordinate positions. The research addresses three main questions. First, how does women’s subordination appear within the patriarchal system of the pesantren? Second, what negotiation strategies do women use to gain space and authority? Third, how do Islamic pesantren women produce authority within patriarchal domination? The study uses a qualitative approach with a multi-site case study method. Data were collected through structured interviews, participant observation, and document analysis in several pesantren. The results show, first, that women’s subordination appears in four forms: structural, normative, cultural, and linguistic. Second, women negotiate these conditions through subtle, ethical, and adaptive strategies. Third, women build their authority through everyday ethical practices, which gradually become cultural and symbolic capital. This process helps them gain cultural recognition that eventually leads to formal acknowledgment. These findings contribute to gender studies in Islamic education by highlighting the active role of pesantren women in challenging and reshaping unequal power relations.